2012
DOI: 10.1161/circulationaha.111.083451
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Abdominal Aortic Aneurysm Formation Is Mediated by IL-17 and Attenuated by Mesenchymal Stem Cell Treatment

Abstract: Background Abdominal aortic aneurysm (AAA) formation is characterized by inflammation, smooth muscle activation and matrix degradation. This study tests the hypothesis that CD4+ T cell-produced IL-17 modulates inflammation and smooth muscle cell activation leading to the pathogenesis of AAA and that human mesenchymal stem cell (MSC) treatment can attenuate IL-17 production and AAA formation. Methods and Results Human aortic tissue demonstrated a significant increase in IL-17 and IL-23 expression in AAA patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
154
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 26 publications
7
154
1
Order By: Relevance
“…As reported by Sharma et al, 15 IL-17 plays a critical role in promoting inflammation during AAA formation. However, in a recent study performed by Ziad Mallat et al, overexpression of suppressor of cytokine signaling 3 in T cells and neutralization of TGF-β activity markedly reduced IL-17 production and increased the aneurysm severity.…”
mentioning
confidence: 65%
“…As reported by Sharma et al, 15 IL-17 plays a critical role in promoting inflammation during AAA formation. However, in a recent study performed by Ziad Mallat et al, overexpression of suppressor of cytokine signaling 3 in T cells and neutralization of TGF-β activity markedly reduced IL-17 production and increased the aneurysm severity.…”
mentioning
confidence: 65%
“…Since CD4 + T cells are divided into Th1, Th2, Th17, Th22, and Th9 (24), and most studies focused only on Th1 (secreting IFN-γ) and Th17 (secreting IL-17), which are believed to predominantly contribute to the pathological changes in autoimmune and inflammatory aneurysm (25,26), we selected IL-17 and IFN-γ for use in this study. First, we performed immunohistochemistry on our mouse samples and determined that IFN-γ and IL-17 were expressed in the inflammatory cells (Supplemental Figure 6A).Then, to investigate whether these cytokines play a role in our model, we crossed our mice into a C57BL/6 background for at least 6 generations and generated IFN-γ-and IL-17-deficient Smad3 +/-mice.…”
Section: Smad3 -/-Cd4 + T Cells Secrete Gm-csf Which Is Important Inmentioning
confidence: 99%
“…The contribution of IL-17 in aneurysm development may be related to its role in modulating SMCs activation. Therefore, the depletion of IL-17 showed attenuated aortic diameter and cytokine production [46]. This theory was confirmed by Ju et al [47], who found that IL-6-signal transducer and activator of transcription-3 (IL-6-STAT3) signaling pathway contributed to Th17 recruitment, promoting aneurysm formation.…”
Section: Th17 Cellsmentioning
confidence: 71%
“…Accumulation of reports document that CD8 + T cells infiltrate aneurysm lesion both from human and mice tissues [13,14,17,26,31,46,54,[64][65][66][67][68][69][70][71]. The predominant cell types within the infiltrate in AAA tissues are CD3 + T cells (more than 50%), including CD4 + T cells and CD8 + T cells [17].…”
Section: Cd8 + T Cellsmentioning
confidence: 99%